DIAGNOSTIC ACCURACY OF FOCUSED ASSESSMENT WITH SONOGRAPHY IN TRAUMA FOR VISCERAL INJURIES IN BLUNT ABDOMINAL TRAUMA PATIENTS KEEPING CT AS GOLD STANDARD - Siraj, Syeda Komal; Akram, Faiza; Shah, Syed Salahuddin; Khan, Waheed; Zeb, Saima (Pakistan Journal of Physiology, 2022)
Background: Blunt abdominal trauma is common and is associated with intra-abdominal injury. Focused assessment with sonography in trauma (FAST) is extremely sensitive and specific test for the diagnosis of visceral injury in such patients with added benefit of quick scan and bedside availability. This study was conducted with an aim to establish the diagnostic accuracy of FAST for diagnosing visceral injuries in blunt abdominal trauma patients. Methods: This study involved 247 patients of both genders aged 18–60 years, referred to Department of Diagnostic Radiology with history of blunt abdominal trauma. All these 247 patients underwent FAST and CT abdomen. The results of CT scan were taken as gold standard and those of FAST were judged accordingly as true/false positive/negative. Results: Visceral injury was diagnosed in 167 (67.6%) patients on FAST while CT scan confirmed visceral injury in 165 (66.8%) patients. There were 155 true positive, 12 false positive, 10 false negative and 70 true negative cases which yielded 93.94% sensitivity, 85.37% specificity, 91.09% accuracy, 92.81% positive predictive value and 87.50% negative predictive value for FAST in detecting visceral injury. Conclusion: FAST is fairly sensitive, specific, and accurate in diagnosing visceral injury among blunt abdominal trauma. Its non-invasive, radiation-free nature, and widespread bedside availability advocate its preferred use in place of CT in diagnosis of visceral injury in blunt abdominal trauma cases. Pak J Physiol 2022;18(3):7?10